Wspólny system obliczania podstawy opodatkowania podatkiem korporacyjnym - Kluzek, Marta (Common Consolidated Corporate Tax Base, 2008)
Different rules of corporate tax in each member country of the European Union negatively influence the competition system of the common market and costs of corporations which have to cope with tax regulations in many jurisdictions. For that reason there are attempts to co-ordinate tax policy in this area. Common Consolidated Corporate Tax Base (CCCTB) is the most probable system that can be used in the future. Tax division among countries could be realized by adopting arm's length principle of formula apportionment. But not all members of the European Union agree with the idea of Common Consolidated Corporate Tax Base and we cannot expect a common solution very fast.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 288-295